The sum of us : how racism hurts everyone : adapted for young readers - McGhee, Heather, 1980- (Delacorte Press, 2023)
"This book, edited for young readers, is a call to action. McGhee examines how damaging racism is not only to people of color but also to white people. She offers hope and real solutions so that we can all prosper. An expert in economic policy, Heath McGhee draws lessons from her work running a think tank and her travels around the country talking to everyday Americans who are coming together to fight for a more just and inclusive society. The people she meets prove how much the stories we tell ourselves about race and belonging influence the policies that determine our shared economic future."--